2021
DOI: 10.1016/j.bonr.2021.101012
|View full text |Cite
|
Sign up to set email alerts
|

Dominant and nondominant distal radius microstructure: Predictors of asymmetry and effects of a unilateral mechanical loading intervention

Abstract: Most information about distal radius microstructure is based on the non-dominant forearm, with little known about the factors that contribute to bilateral asymmetries in the general population, or what factors may influence bilateral changes over time. Here, we analyzed bilateral high resolution peripheral quantitative computed tomography (HRpQCT) data collected over a 12-month period as part of a clinical trial that prescribed a well-controlled, compressive loading task to the nondominant forearm. Baseline da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…One study has shown that the bone mineral density, as measured by DEXA, from the femur and distal radius showed significant differences between the two sites (Wilson et al 2009). Additionally, handedness has been shown to cause asymmetries in the thickness and BMD of bone between the left and right sides of the body due to habitual loads (Troy et al 2021) This could explain the internal inconsistencies observed between correlations of the dominant and nondominant sides.…”
Section: Mechanical Properties At the Hipmentioning
confidence: 99%
“…One study has shown that the bone mineral density, as measured by DEXA, from the femur and distal radius showed significant differences between the two sites (Wilson et al 2009). Additionally, handedness has been shown to cause asymmetries in the thickness and BMD of bone between the left and right sides of the body due to habitual loads (Troy et al 2021) This could explain the internal inconsistencies observed between correlations of the dominant and nondominant sides.…”
Section: Mechanical Properties At the Hipmentioning
confidence: 99%
“…However, to apply the mechanism of human arm control to robots, it is necessary to understand the similarities and differences between the dominant and non-dominant hands. Tasks performed with control from both arms are known to involve laterality [1][2][3][4][5][6][7][8][9]. It has been widely postulated that one cause of this phenomenon is the living environment and functional difference in the development of both arms [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%